Current state of dental bleaching - Lamas-Lara, César (2014)
One of the most popularized treatments required by patients is the dental bleaching; this procedure has fairly predictable results, easy to perform, noninvasive, but is one of the procedures that the profesional has more doubts to do it, sometimes we make use of techniques and procedures that lack scientific support and lead to unsatisfactory results. This article presents a literature review and is performed a sequence that can guide the professional for proper protocol in the dental bleaching in different clinical situations. It is essential to make a correct diagnosis, not only when dental whitening procedures but in any proceedings, as well as to offer an approach from various perspectives interrelating the various specialties of dentistry in order to achieve the best possible results.